Globalisation Affects the Economic Situation of Mexican Women - Królik, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The purpose of the article was the answer to determine whether globalization has an impact on the economic situation of women in Mexico. It also presents the current model of life and its impact on the situation of people in the poorest countries. Today, thanks to the media, information quickly orbits the entire globe, reaching even its remotest corners. Therefore, in Mexico they are beginning to apply standards which until recently were only applied in Europe or North America. The role of women is no longer confined to the role of wives and mothers, they are becoming professionally and socially active. However, there is still a lot to be done in Mexico. First of all, there is a need for greater understanding and support of society as a whole. Men and women alike should get involved in the fight to improve the situation of working women, as well as creating equal opportunities for them on the labour market. The phenomenon of globalisation involves changes in all spheres of life all over the globe. The situation of women living in developing countries is improving every year, mainly due to greater public awareness and understanding of the necessary changes. The role of the State, which has to this point been negligible, is also of great importance. However, the forecasts are very positive and show there will be a change for the better in the coming years.